Mathematical Communication Skills Reviewed from Self-Efficacy by Using Problem Based Learning (PBL) Model Assisted with Manipulative Teaching Aids - Herdini, Resty Ayu; Suyitno, Hardi; Marwoto, Putut (Journal of Primary Education, 2019)
The purposes of this study were to determine the effectiveness of PBL model assisted with the manipulative teaching aids towards the mathematical communication skills, and to find out the self-efficacy based on the dimensions of magnitude, strenght, and generally. This study applied mixed method type of research with concurrent embedded design. The sample in this study is 9 students consist of 3 students in the magnitude dimension, 3 students in the strength dimension, and 3 students in the generally dimension that had been determined based on the written and oral Mathematical Communication Ability Tests (TKKM). The instruments used to collect data in this study consists of learning aids or devices such as, written TKKM Tests, questionnaire sheet and interview guidelines. The techniques of collecting data were conducted by using questionnaires, tests and interviews. The effectiveness was described based on (1) the average completeness test of 0.436; (2) the average difference test of 2.867; and (3) N-gain test of 0.468. The results of this study showed that learning conducted by using problem based learning model assisted with manipulative teaching aids is effective toward the mathematical communication skills. In addition, by using problem based learning model assisted with manipulative teaching aids can improve self efficacy in its every dimensions, including: the dimensions of magnitude obtain an average of 82.32; the dimension of strength gained an average of 80.37; and the dimensions of generally get an average of 81.78.